10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
ObjectiveThis study aimed to investigate central sensitization (CS) in individuals with lipedema using pressure pain threshold measurements and to examine its relationship with clinical features, sonographic findings, body composition, and Central Sensitization Inventory (CSI) scores.MethodsA total of 61 female patients with lipedema and 20 healthy controls were included in this cross-sectional study. Pressure pain threshold (PPT) was assessed at the thigh, pretibial region, and forearm using a manual algometer. Sonographic subcutaneous fat thickness was evaluated, and body composition parameters were assessed using bioelectrical impedance analysis. Clinical outcomes related to CS-including the CSI, Visual Analog Scale (VAS), Lower Extremity Functional Scale (LEFS), Short Form-12 (SF-12), and the Extended Nordic Musculoskeletal Questionnaire (NMQ-E)-were recorded. Linear mixed-effects models were used to compare PPT across groups, anatomical sites, and disease stages. Associations between PPT, CSI scores, body composition parameters, sonographic findings, and clinical measures were evaluated using Pearson correlation analyses.ResultsPatients with lipedema exhibited significantly lower PPT values across all anatomical regions, including the forearm, and significantly higher CSI scores compared with healthy controls (p < .001). Sonographic assessment confirmed increased subcutaneous fat thickness in the lower extremities of lipedema patients. Lipedema stage was not associated with overall PPT levels. However, lower forearm PPT and LEFS scores were observed in more advanced stages. Forearm PPT showed significant negative correlations with lean body mass, body fat mass, and total body water (p < .05), while no other significant associations were identified.ConclusionIndividuals with lipedema demonstrate features consistent with CS, characterized by reduced PPTs in both affected and non-affected regions together with elevated CSI scores. These findings suggest that altered pain processing may contribute to the widespread pain and functional limitations observed in lipedema, highlighting the importance of comprehensive assessment of CS in this population.